Identifikasi Interaksi Obat Pada Pasien Lansia Yang Berisiko Sindrom Metabolik Di Puskesmas Aikmel - Sovia, Fitriwati; Hardiyanti, Novi; Rafsanjani, Arief; Oktresia, Erma Ewisa (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Metabolic syndrome is an increasingly prevalent health problem in both developed and developing countries, including Indonesia. The treatment of metabolic syndrome often involves polypharmacy, which increases the potential for drug interactions. Drug interactions are considered clinically important if they can cause increased toxicity or reduce the therapeutic effects of drugs, leading to a failure to achieve the desired therapeutic effect. Reported cases of drug interactions are more common in elderly patients. This study aims to determine the potential Drug-drug Interactions (DDIs) in elderly patients at risk of metabolic syndrome at Puskesmas Aikmel. The study uses a descriptive observational method with prospective data collection. The population in this study consists of outpatient patients at Puskesmas Aikmel from May to July 2021, meeting the inclusion criteria: patients diagnosed at risk of metabolic syndrome, elderly patients (age ? 60 years), and using a minimum of 2 drugs. Sampling was done using total sampling technique. The results of the study indicate 99 cases of potential drug interactions identified in the prescription of elderly patients. The drug classes with potential interactions include antihypertensive drugs in 51 (51.51%) cases, antihyperglycemic drugs in 42 (42.42%) cases, and dyslipidemia drugs in 6 (6.06%) cases. The types of drug interactions observed were pharmacokinetic interactions in 37 (37.37%) cases, pharmacodynamic interactions in 58 (58.58%) cases, and unknown interactions in 4 (4.04%) cases. The severity of these potential interactions was classified as minor in 5 (5.05%) cases, moderate in 86 (86.87%) cases, and major in 8 (8.08%) cases.